The Impact of Learning Strategies on English Proficiency: Insights from UNM English Department Students - Afif Zuhdy Idham; Ahmad Fadhil Imran; Ahmad Fathir Imran; Wahyuddin Rauf (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This study aimed to explore the most commonly used language learning strategies among English department students at Universitas Negeri Makassar (UNM), assess their proficiency level based on TOEFL scores, and examine the relationship between their learning strategies and proficiency level. A correlational research design was applied, involving fourth-semester students from three study programs: English Education, English Literature, and Business English. The participants were selected through accidental sampling, focusing on students who took the TOEFL test provided by the English department's Centre for Language Services (CLS). Data collection was conducted using the SILL questionnaire and TOEFL score documentation, and analysis was performed through descriptive and inferential statistics using SPSS. The findings revealed that metacognitive and social strategies were the most frequently used language learning strategies, falling within the high usage category. In terms of proficiency, students were classified at the basic user level based on their TOEFL scores. Additionally, the study found no significant correlation between students’ language learning strategies and their proficiency level, as the statistical analysis results indicated no meaningful association between the two variables.